2021
DOI: 10.1007/s10461-021-03502-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV Serostatus Disclosure Among Men Who Have Sex with Men in China in the Era of U=U and PrEP

Abstract: Given the recent evidence on “Undetectable = Untransmittable” (U=U) and pre-exposure prophylaxis (PrEP), the present study aimed to investigate HIV disclosure behaviors and their associations with sexual risk behaviors and U=U and PrEP awareness among men who have sex with men (MSM) in China. A cross-sectional survey was conducted among 689 MSM recruited through a gay-friendly non-governmental organization located in Chengdu, China in 2018–2019. Information was collected by a structured self-administrated ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…Finally, previous studies indicated that HIV testing is positively associated with HIV serostatus request and disclosure [ 22 , 27 ], and our study found corroborating results. Furthermore, MSM who had higher HIV testing social norm scores and had intervened in any HIV-related programs were more likely to request HIV serostatus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, previous studies indicated that HIV testing is positively associated with HIV serostatus request and disclosure [ 22 , 27 ], and our study found corroborating results. Furthermore, MSM who had higher HIV testing social norm scores and had intervened in any HIV-related programs were more likely to request HIV serostatus.…”
Section: Discussionsupporting
confidence: 91%
“…Only a few studies have investigated HIV serostatus request behavior, and our data contribute to the literature [ 5 , 6 ]. Some influence factors have been identified in studies, such as perceived high HIV risk, lower HIV-related stigma, and greater engagement with the MSM community [ 26 , 27 ]. HIV serostatus request, as a proactive behavior, which can elevate the importance of consciousness about HIV serostatus disclosure before sex, has ample room for improvement among MSM.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated that MSM who had undergone HIV testing in the last 3 months were more likely to be aware of their partner's HIV serostatus. This nding is in line with previous studies analyzing factors associated with HIV serostatus disclosure and demonstrates that the lack of HIV testing was one of the main reasons for low HIV serostatus disclosure among Chinese MSM [25,27,29]. HIVST as a complement to conventional facility-based HIV testing services, is expected to promote HIV serostatus disclosure among MSM.…”
Section: Discussionsupporting
confidence: 90%